Role of Criminal Law in Falsification of Covid-19 Vaccine Certificates - Mochamad Faishal Hafizh; Grasia Kurniati; Rani Apriani (Peneliti.net, 2022)
During the current pandemic, the importance of a Covid-19 vaccination certificate encourages people to carry out vaccination activities. However, it becomes a problem when a few people who are afraid of vaccination make an illegal agreement with the health services to fake or get a vaccine certificate without having to vaccinate in exchange for money. This refers to Law.Number.198of 2016 Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions, which are said to.be criminal acts with a threat of 12 years in. prison and.a fine of 12.billion. The approach.method.used.in this.research.is.normative juridical, namely by combining.secondary.and doctrinal legal regulations that are applied to the issues discussed. The existence of the Ministry of Communication and Information is.regulated in Presidential Regulation-of9the.Republic of Indonesia. Number 54 of 2015 which.essentially assists the president in administering the state government which regulates everything related to documentation or electronic mail. also has the authority to oversee criminal acts of falsification of certificates or documents assisted by the police against irresponsible persons